Photovoltaic glass, preparation method thereof and photovoltaic module

By adding ZnO and/or Li2O to the photovoltaic glass to optimize its chemical composition, the problem of low ultraviolet light transmittance in existing photovoltaic glass is solved, and the effect of improving the photoelectric conversion efficiency of photovoltaic modules is achieved.

CN119638190APending Publication Date: 2025-03-18DAS SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311188249.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The ultraviolet transmittance of existing photovoltaic glasses is not high, which makes photovoltaic modules unable to effectively utilize the ultraviolet light in the sunlight, affecting the photoelectric conversion efficiency.

Method used

By adding ZnO and/or Li2O to the composition of the photovoltaic glass, the chemical composition of the glass is adjusted to include SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, ZnO and Li2O, the thermal expansion coefficient, chemical stability and ultraviolet transmittance of the glass are optimized.

Benefits of technology

The ultraviolet transmittance of photovoltaic glass is improved, the thermal expansion coefficient, heat resistance and chemical stability of the glass are enhanced, thereby improving the photoelectric conversion efficiency of photovoltaic modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638190A_ABST
    Figure CN119638190A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides photovoltaic glass, a preparation method thereof and a photovoltaic module, and the photovoltaic glass comprises the following components: SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, ZnO and / or Li2O. According to the embodiment of the invention, ZnO and / or Li2O are / is added in the glass components, and Li2O can replace Na2O or K2O, so that the thermal expansion coefficient of the glass is reduced, the heat resistance and strength of the glass are enhanced, and the ultraviolet transmittance of the glass can be improved; znO can reduce the thermal expansion coefficient of the glass, improve the chemical stability of the glass and reduce the influence of Na ions on the water resistance of the glass, and also can improve the ultraviolet transmittance of the glass; therefore, the problem of low ultraviolet light transmittance of the existing photovoltaic glass provided by the invention is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic manufacturing technology, and in particular to photovoltaic glass and a preparation method thereof, and a photovoltaic module. Background Art

[0002] Currently, due to the development of the photovoltaic industry, photovoltaic modules are widely used.

[0003] However, the photovoltaic glass in existing photovoltaic modules is mainly soda-lime glass, which can absorb all light below 310nm and has a transmittance of less than 70% for light between 310 and 380nm, resulting in low utilization rate of ultraviolet light by photovoltaic modules. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a photovoltaic glass and a preparation method thereof, and a photovoltaic module, so as to solve the problem that the ultraviolet light transmittance of the existing photovoltaic glass is not high.

[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:

[0006] The present invention provides a photovoltaic glass, wherein the components constituting the photovoltaic glass include SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, and also include ZnO and / or Li2O.

[0007] Furthermore, in the photovoltaic glass, the mass percentage of ZnO is 0-5%.

[0008] Furthermore, in the photovoltaic glass, the mass percentage of ZnO is 0.5-1.5%.

[0009] Furthermore, in the photovoltaic glass, the mass percentage of Li2O is 0-2%.

[0010] Furthermore, in the photovoltaic glass, the mass percentages of SiO2, Al2O3, CaO, MgO, Na2O, K2O and Sb2O3 are 70-76%, 0-1%, 5-10%, 1-6%, 5-12%, 0-2% and 0-0.5% respectively.

[0011] Furthermore, the components constituting the photovoltaic glass include SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, ZnO and Li2O, and the mass percentages of SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, ZnO and Li2O are 75%, 0.5%, 8.5%, 5.5%, 8%, 1%, 0.25%, 1% and 0.4% respectively.

[0012] The present invention also provides a method for preparing photovoltaic glass, which comprises:

[0013] After quartz glass is granulated, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, and ZnO and / or Li2O are added and melted to obtain a first slurry;

[0014] Passing a reducing gas into the first slurry for a reduction reaction to obtain a second slurry, wherein the reducing gas is a mixed gas of H2 and CO;

[0015] The second slurry is clarified, homogenized, formed, processed and annealed to obtain photovoltaic glass.

[0016] Furthermore, in the preparation method, the volume percentage of H2 in the reducing gas is greater than or equal to 80% and less than 100%.

[0017] Furthermore, in the preparation method, the reducing gas is produced and obtained using photovoltaic carbon fixation technology.

[0018] The present invention further proposes a photovoltaic assembly, which includes a stacked backplane, solar cells and the photovoltaic glass as described above, wherein the solar cells are located between the photovoltaic glass and the backplane.

[0019] Compared with the prior art, the embodiments of the present invention have the following advantages:

[0020] In the embodiment of the present invention, the components constituting the photovoltaic glass include SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, and also include ZnO and / or Li2O. By adding ZnO and / or Li2O to the glass components, wherein Li2O can replace Na2O or K2O, not only the thermal expansion coefficient of the glass is reduced, the heat resistance and strength of the glass are enhanced, but also the ultraviolet transmittance of the glass can be improved, and ZnO can reduce the thermal expansion coefficient of the glass, improve the chemical stability of the glass, and reduce the influence of Na ions on the water resistance of the glass, and can also improve the ultraviolet transmittance of the glass; therefore, the problem of low ultraviolet transmittance of the existing photovoltaic glass provided by the present invention is solved.

[0021] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a flow chart of a method for preparing photovoltaic glass provided by an embodiment of the present invention;

[0023] Figure 2 is a design flow chart of the photovoltaic glass formula in an embodiment of the present invention;

[0024] Figure 3 It is a schematic diagram of the structure of a double-glass photovoltaic module provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0026] According to the different wavelengths of ultraviolet rays themselves, ultraviolet rays can be divided into near ultraviolet (UVA), far ultraviolet (UVB) and ultra-short ultraviolet (UVC). The wavelength of near ultraviolet is 315-400nm, the wavelength of far ultraviolet is 280-315nm, and the wavelength of ultra-short ultraviolet is 100-280nm.

[0027] Due to the presence of the ozone layer in the atmosphere, ultraviolet light with a wavelength of 240 to 280nm in sunlight will be strongly absorbed, resulting in almost no ultraviolet light signals in this band in near-Earth space, thus forming a "solar blind zone" that prevents photovoltaic modules from receiving ultraviolet light below 280nm; and photovoltaic glass is mainly made of soda-lime glass, which will absorb all light below 310nm, and the transmittance of 310 to 380nm is less than 70%, or even lower, which ultimately leads to the inability of photovoltaic modules to effectively utilize the ultraviolet light in sunlight, affecting the photoelectric conversion efficiency of the modules.

[0028] The applicant of the present invention has found that impurities in glass are often an important factor causing ultraviolet light absorption. For photovoltaic glass with high transmittance, the impurity content must be as low as possible. In order to reduce the impurities in the material, the preparation conditions of the material are usually made more rigorous and demanding.

[0029] Among them, transition metals Ce, Pt, Cu, Fe, and Ni can all cause absorption at 150 to 350 nm. 2+ It exists in divalent form in glass and has a strong absorption band at 170nm; Ce 4+ It has strong ultraviolet absorption at 270nm, while Ce 3 + There is absorption at 208nm, 220nm, 245nm and 260nm. Ce ion impurities will cause a wider absorption band. Cr is the most stable element in the glass melt. 3+ , causing strong absorption at 218nm and weak absorption at 440nm, making the glass green; copper in glass is Cu + and Cu 2+ The copper-containing glass has strong absorption at 175nm, 180nm and 230nm, especially the absorption at 230nm is attributed to copper ions in two valence states at the same time; Fe 2+and Fe 3+ Both absorb ultraviolet light, with the former absorbing at 170nm and 220nm, and the latter at 185nm and 260nm. 3+ and Ti 4+ 、V 3+ and V + 、Co 2+ , Pb 2+ They all have strong absorption in the ultraviolet band.

[0030] For Fe 3+ The absorption coefficient ε has a peak value of 0.18 cm at a wavelength of 260 nm. -1 ppm -1 , much higher than Fe 2+ Peak at 220nm 0.0055cm -1 ppm -1 This leads to a huge difference in the UV transmittance of glass with different valence iron ion impurity contents. When the iron ion content continues to decrease to 6ppm, the Fe 3+ The transmittance of the glass is still only 10%. As for the negative impact on UV transmittance, the high-valent iron ions produced in an oxidizing atmosphere are greater than the low-valent iron ions produced in a reducing atmosphere. In addition, Cu + and Cu 2+ It also exhibits the same properties.

[0031] At the same time, the water content in the glass also affects the UV transmittance. Specifically, as the water content increases, λ0 moves toward the long wave. For every 1 ppm increase in water content, λ0 moves 6 nm toward the long wave direction.

[0032] In addition, melting in a reducing atmosphere can further reduce the valence of impure metal ions in the glass, thereby improving the ultraviolet transmittance of the glass.

[0033] For weather resistance, when the network connection is low (i.e., the non-bridging oxygen content is high), the atomic packing density of the glass is large and the molar volume is relatively low, resulting in a higher elastic modulus and Poisson's ratio, and its hardness and brittleness values ​​are also higher, while the toughness value is low and the crack resistance is relatively weak; on the contrary, when the network connection is high, the viscosity of the glass is high and has a smaller thermal expansion coefficient. Densification takes advantage during the indentation process, and the higher the degree of densification of the glass, the stronger its crack resistance.

[0034] As the MgO / CaO ratio increases, the transition temperature Tg of the glass gradually increases, the thermal expansion coefficient gradually decreases, and the hardness and brittleness of the glass both show a trend of first decreasing and then increasing, reaching the minimum value (Hv) when MgO / CaO = 1 (HDM3). min =5.36GPa, B min =5μm-1 / 2 ). The crack resistance and toughness of the glass first increase and then decrease with the increase of MgO / CaO ratio, while the Young's modulus and shear modulus remain basically unchanged.

[0035] In oxide glass, network forming body ions have the greatest influence on the glass expansion coefficient, followed by network modifier ions. As the radius of the modifier ion increases, its influence on the glass expansion coefficient also increases. This is because it plays a "network breaking" role in the glass network structure, resulting in the breaking of silicon-oxygen bonds, reducing the bridging oxygen content, and reducing the degree of glass network connection. Moreover, at high temperatures, the thermal expansion coefficient increases due to the poor ability of alkali metal oxides to resist thermal vibrations.

[0036] The higher the network connection of the glass sample, the better its crack resistance. Specifically, as the indentation load increases, various cracks will appear on the surface and inside the glass. When the load is small, radial cracks appear on the glass surface and can be observed by the naked eye. When the load is large, conical cracks, transverse cracks and median cracks will appear on the sample surface.

[0037] In addition, with the increase of the indentation depth recovery rate, the crack resistance of the glass is gradually improved, indicating that the glass that is easy to densify can effectively reduce the residual stress around the indentation, thereby improving its crack resistance. The actual stress distribution around the indentation is relatively complex, and it changes dynamically during the indentation process. In addition, other types of cracks will also be formed. Their distribution and changes mainly depend on the combination of various mechanical properties of the glass, resulting in differences in crack initiation behavior (such as initial load, position, direction and crack type) between different glass compositions. More noteworthy is that the atmosphere also affects the initiation and propagation of cracks. Crack initiation is very sensitive to moisture, and its sensitivity depends on the glass composition.

[0038] For glass, any tiny surface feature will directly lead to a sharp drop in strength, such as stress corrosion cracking, subcritical crack growth, delayed failure and static fatigue, which is caused by crack growth when the glass is stressed in the presence of moisture or other active substances. These surface defects are pre-existing or caused by processing. Other defects such as pores and other volume defects will not affect the external environment because they are not exposed to it. Since it is the partial pressure of active substances in the environment that controls the rate of crack growth, as long as the environment is not completely inert, it will cause stress corrosion and reduce the strength of the glass. This environment can refer to moisture in the air or impurities dissolved in the liquid.

[0039] Based on the above findings, in order to solve the above problems, an embodiment of the present invention provides a photovoltaic glass, wherein the components constituting the photovoltaic glass include SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, and also include ZnO and / or Li2O.

[0040] Among them, SiO2 can increase the viscosity of glass liquid, reduce the crystallization tendency of glass, improve the chemical stability and thermal stability of glass, the mechanical strength and transparency of glass, etc., and the density and thermal expansion coefficient of glass decrease with the increase of SiO2 content.

[0041] Among them, a small amount of Al2O3 is a tetrahedral structure in the glass, which plays the role of repairing the network. In addition, Al2O3 can reduce the crystallization tendency and crystallization speed of glass, reduce the expansion coefficient of glass, and improve the viscosity, surface tension, softening temperature, thermal stability, chemical stability and mechanical strength of glass. It is an effective glass stabilizer. However, the influence of Al2O3 on increasing the viscosity of glass is greater than that of SiO2, which will slow down the melting speed and prolong the clarification time, and easily form ribs and lines on the glass plate surface; at the same time, it is not conducive to the polishing, flattening and thinning of the glass liquid in the tin bath.

[0042] Among them, CaO can improve the mechanical strength, hardness and chemical stability of glass. An appropriate amount of CaO can reduce the viscosity of glass liquid at high temperature, which is beneficial to refining and clarification. At low temperature, it can increase the point of glass liquid, accelerate the hardening speed, and is beneficial to the rapid molding of glass. However, CaO will increase the crystallization tendency of glass, so the CaO content in glass should not be too high. If it is greater than 10%, the glass will become brittle and the molding difficulty will increase.

[0043] Among them, an appropriate amount of MgO can reduce the high-temperature viscosity of glass, reduce the crystallization tendency and crystallization speed of glass, improve mechanical strength and chemical stability, and also have a good effect on improving the thermal stability of glass. The content of MgO should be increased accordingly when producing ultra-thin glass. MgO has a complex effect on the viscosity of glass. Specifically, when the temperature is higher than 1200°C, it will reduce the viscosity of the glass liquid; and between 900 and 1200°C, it tends to increase the viscosity of the glass liquid. Therefore, the MgO content in the glass should not be too large.

[0044] Among them, Na2O can reduce the melting temperature of glass, greatly reduce the viscosity of glass liquid, increase the high-temperature fluidity of glass liquid, and is a good co-solvent. Too much Na2O content will reduce the mechanical strength, chemical stability and thermal stability of glass, increase the glass expansion coefficient, make the glass brittle, and easily cause the glass to alkali precipitate and mold, increasing the cost of glass production; therefore, the Na2O content in the glass composition cannot be too high, and a small amount of K2O is used instead, which has a "double alkali effect", can improve the chemical stability of glass, and significantly reduce crystallization. Specifically, the introduction of K2O in float glass production can greatly reduce the surface tension of glass, which is beneficial to the flattening and polishing of glass liquid in the tin bath, obtain high-quality glass surface, and improve the gloss of glass.

[0045] Among them, the role of Li2O in glass is more special than that of Na2O and K2O. The ion radius of lithium is smaller than that of sodium and potassium. Li2O replaces Na2O or K2O to reduce the thermal expansion coefficient of glass and reduce the crystallization tendency. Introducing a small amount of Li2O into glass can reduce the melting temperature of glass and improve the output and quality of glass, but excessive Li2O increases the crystallization tendency.

[0046] Among them, adding ZnO to the glass composition can reduce the thermal expansion coefficient of the glass, improve the chemical stability of the glass, and make the material properties longer. It is usually used when dissolving chemical-resistant glass and low-soluble glass.

[0047] Based on the above principle, in the embodiment of the present invention, by adding ZnO and / or Li2O to the glass composition, wherein Li2O can replace Na2O or K2O, not only the thermal expansion coefficient of the glass is reduced, the heat resistance and strength of the glass are enhanced, but also the ultraviolet transmittance of the glass can be improved, and ZnO can reduce the thermal expansion coefficient of the glass, improve the chemical stability of the glass, and reduce the influence of Na ions on the water resistance of the glass, and can also improve the ultraviolet transmittance of the glass; therefore, the problem of low ultraviolet transmittance of the existing photovoltaic glass provided by the present invention is solved.

[0048] Optionally, in one embodiment, the components constituting the photovoltaic glass include ZnO, and the mass percentage of ZnO in the photovoltaic glass is 0-5% and not zero, which can not only effectively improve the problem of low ultraviolet light transmittance, but also significantly increase the softening point temperature of the glass, thereby reducing the thermal expansion coefficient of the glass and significantly enhancing the heat resistance and strength of the glass.

[0049] Optionally, in a specific embodiment, the mass percentage of ZnO in the photovoltaic glass is 0.5-1.5%, for example, it can be a range of one or any two of 0.5%, 1%, and 1.5%.

[0050] Optionally, in a specific embodiment, the components constituting the photovoltaic glass include Li2O, and the mass percentage of Li2O in the photovoltaic glass is 0-2% and is not zero, for example, it can be 0.05%, 0.1%, 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2% or any two of the range values.

[0051] Optionally, in one embodiment, in the photovoltaic glass, the mass percentages of SiO2, Al2O3, CaO, MgO, Na2O, K2O, and Sb2O3 are 70-76%, 0-1%, 5-10%, 1-6%, 5-12%, 0-2%, and 0-0.5%, respectively, which can effectively take into account the mechanical strength, chemical stability, and thermal stability of the glass. Optionally, the mass percentage of SiO2 can be 73% to 75%, the mass percentage of Al2O3 can be 0% to 0.5% and not zero, and the mass percentage of MgO can be 1% to 5%.

[0052] Optionally, in a specific embodiment, the components constituting the photovoltaic glass include SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, ZnO and Li2O, and the mass percentages of SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, ZnO and Li2O are 74.85%, 0.5%, 8.5%, 5.5%, 8%, 1%, 0.25%, 1% and 0.4%, respectively, which can effectively take into account the mechanical strength, chemical stability, thermal stability and ultraviolet transmittance of the glass, and its ultraviolet transmittance can reach 80%.

[0053] In addition, impurities such as FeO and Fe2O3 that cannot be removed from quartz sand and are mixed into the glass during production will cause the glass to turn yellow-green and affect the glass's viscosity, thermal permeability, hardening speed and other properties. The Fe in sodium-lime-silica glass is generally Fe 2+ or Fe 3+ Status Status Existence, Fe 3+ The 3d orbital of the ion is half-filled, so the coloring is very weak, making the glass appear light yellow; 2+ It will make the glass light blue, and its coloring ability is better than Fe 3+ Therefore, the mass percentage of Fe2O3 in colorless float glass products is ≤0.08%.

[0054] The present invention also provides a method for preparing photovoltaic glass, wherein: Figure 1 As shown, it includes steps 101 to 103:

[0055] Step 101: After granulating the quartz glass, add Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, and ZnO and / or Li2O, and melt to obtain a first slurry;

[0056] Step 102, introducing a reducing gas into the first slurry for a reduction reaction to obtain a second slurry, wherein the reducing gas is a mixed gas of H2 and CO;

[0057] Step 103: clarify, homogenize, shape, process and anneal the second slurry to obtain photovoltaic glass.

[0058] In the embodiment of the present invention, based on the principle that melting in a reducing atmosphere can further reduce the valence state of impurity metal ions in the glass, thereby improving the ultraviolet transmittance performance of the glass, the quartz glass with a single component of silicon dioxide is first granulated, cleaned and impurities are removed, and then oxides composed of Al2O3, CaO, MgO, Na2O, K2O, Sb2O3 and ZnO and / or Li2O are added and melted, and the molten slurry is passed through a reducing gas composed of a mixture of H2 and CO to reduce the impurity metals to reduce the valence state of impurity metal ions such as Fe, and then clarified, homogenized, formed, processed and annealed, so that photovoltaic glass with high ultraviolet transmittance can be obtained.

[0059] In the above step 101, quartz glass (SiO2) accounting for 70-76% of the total mass of the raw materials, 0-1% of 5-10% of Al2O3, 5-10% of CaO, 1-6% of MgO, 5-12% of Na2O, 0-2% of K2O, 0-0.5% of Sb2O3, and 0-5% and not zero ZnO and / or 0-2% and not zero Li2O are mixed and melted to obtain the above first slurry; wherein the quartz glass can be quartz ore cullet; and the purity of the above components is above 99.5%.

[0060] In the above step 102, the first slurry is passed through a reducing gas composed of H2 and CO, wherein the volume percentage of H2 is greater than or equal to 80% and less than 100%, which can not only effectively reduce Fe 3+ The impurity metal ions are reduced to Fe 2+ By obtaining the second slurry in a low-price state, it can also significantly achieve the effect of carbon reduction and cost reduction.

[0061] Optionally, the volume percentage of H2 in the reducing gas can be one of 80%, 85%, 90%, 90%, 99% or any two of the range values; optionally, the above-mentioned reducing gas can be produced and obtained using photovoltaic carbon fixation technology.

[0062] See also Figure 2, shows a design flow chart of the photovoltaic glass formula in the embodiment of the present invention. As shown in 2, the glass composition is first designed by analyzing the principles of each component, and then the first glass sample is prepared; each first glass sample is subjected to viscosity and chemical stability tests, and the glass component with better viscosity and chemical stability is used as a reasonable glass component, and the second glass sample is prepared using the reasonable glass component, and then various performance tests are performed on it; wherein the various performance tests specifically include: structure test, Raman and FT-IR test, rheological performance test, viscosity test, thermal expansion performance analysis, chemical stability performance test and optical performance tests such as ultraviolet transmittance, so as to screen out an optical glass formula with excellent comprehensive performance.

[0063] The present invention also provides a photovoltaic module, wherein: Figure 3 As shown, it includes a back plate 11 , a solar cell 12 and the photovoltaic glass 13 as described above, which are stacked. The solar cell 12 is located between the photovoltaic glass 13 and the back plate 11 .

[0064] The present invention is described in detail below by way of examples.

[0065] Example 1

[0066] The raw materials are mixed according to the mass ratio shown in Table 1, then melted, and the molten slurry is passed through a reducing gas composed of a mixture of H2 and CO, and then clarified, homogenized, formed, processed and annealed to prepare a finished glass product; wherein the volume percentage of H2 in the reducing gas is 80%.

[0067] Table 1

[0068] Sample No. <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[Sb2O3]]> ZnO <![CDATA[Li2O]]> CS1 71.683 0.56 8.535 3.7 0.372 14.9 0.25 0 0 CS2 71.383 0.56 8.835 3.7 0.372 14.9 0.25 0 0 CS3 71.083 0.56 9.135 3.7 0.372 14.9 0.25 0 0 CS4 70.783 0.56 9.435 3.7 0.372 14.9 0.25 0 0 CS5 70.483 0.56 9.735 3.7 0.372 14.9 0.25 0 0 CS6 70.183 0.56 10.035 3.7 0.372 14.9 0.25 0 0

[0069] The melting temperature, softening point temperature and corrosion resistance of the finished glass products obtained by each sample number in Table 1 were analyzed. The results are shown in Table 2.

[0070] According to Table 2, as the CaO / SiO2 mass ratio increases, the Na ion content decreases relatively, the melting temperature and softening point temperature remain basically unchanged, and the transmittance decay is affected by the local density of the amorphous material inside the glass, and its fluctuation is small. However, due to the decrease in the proportion of SiO2, the transmittance shows a downward trend.

[0071] Table 2

[0072] Sample No. Melting temperature / ℃ Softening point temperature / ℃ PCT48 (121°C, 100% humidity) transmittance attenuation CS1 1150 750 99.65% CS2 1140 740 99.82% CS3 1130 730 99.10% CS4 1120 720 99.27% CS5 1110 710 99.67% CS6 1100 700 99.87%

[0073] Example 2

[0074] The difference between Example 2 and Example 1 is that the raw materials are mixed according to the mass ratio shown in Table 3.

[0075] Table 3

[0076] Sample No. <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[Sb2O3]]> ZnO <![CDATA[Li2O]]> Z0 71 0.3 9.67 5 0.03 14 0 0 0 Z1 71 0.3 9.67 5 0.03 13 0 1 0 Z2 71 0.3 9.67 5 0.03 12 0 2 0 Z3 71 0.3 9.67 5 0.03 11 0 3 0 Z4 71 0.3 9.67 5 0.03 10 0 4 0 Z5 71 0.3 9.67 5 0.03 9 0 5 0

[0077] The melting temperature, softening point temperature and corrosion resistance of the finished glass products obtained by each sample number in Table 3 were analyzed. The results are shown in Table 4.

[0078] According to Table 4, with the increase of the ZnO / SiO2 mass ratio, the addition of ZnO and other mixed materials dilutes the concentration of SiO2 and reduces the Na ions. Therefore, the melting temperature and softening point temperature of the finished glass tend to increase, and the corrosion resistance is also improved.

[0079] Table 4

[0080] Sample No. Melting temperature / ℃ Softening point temperature / ℃ PCT48 (121°C, 100% humidity) transmittance attenuation Z0 1200 810 99.64% Z1 1210 820 99.98% Z2 1220 830 99.53% Z3 1230 840 99.91% Z4 1240 850 99.63% Z5 1250 860 99.28%

[0081] Example 3

[0082] The difference between Example 3 and Example 1 is that the raw materials are mixed according to the mass ratio shown in Table 5.

[0083] Table 5

[0084] Sample No. <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[Sb2O3]]> ZnO <![CDATA[Li2O]]> L0 71 0.3 9.67 5 0.03 14 0 0 0 L1 71 0.3 9.67 5 0.03 13.6 0 0 0.4 L2 71 0.3 9.67 5 0.03 13.2 0 0 0.8 L3 71 0.3 9.67 5 0.03 12.8 0 0 1.2 L4 71 0.3 9.67 5 0.03 12.4 0 0 1.6 L5 71 0.3 9.67 5 0.03 12 0 0 2

[0085] The melting temperature, softening point temperature and corrosion resistance of the finished glass products obtained by each sample number in Table 5 were analyzed. The results are shown in Table 6.

[0086] According to Table 6, as the LiO / SiO2 mass ratio increases, the SiO2 and Na ions decrease relatively, causing the melting temperature and softening point of the finished glass to increase continuously, and the corrosion resistance is also improved.

[0087] Table 6

[0088] Sample No. Melting temperature / ℃ Softening point temperature / ℃ PCT48 (121°C, 100% humidity) transmittance attenuation L0 1200 800 99.76% L1 1210 810 99.19% L2 1220 820 99.10% L3 1230 830 99.54% L4 1240 840 99.55% L5 1250 850 99.63%

[0089] Example 4

[0090] The difference between Example 4 and Example 1 is that the raw materials are mixed according to the mass ratio shown in Table 7.

[0091] Sample No. <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[Sb2O3]]> ZnO <![CDATA[Li2O]]> <![CDATA[Na0]]> 70.75 0.5 8.5 5.5 0.5 14 0.25 0 0 <![CDATA[Na1]]> 70.85 0.5 8.5 5.5 1 12 0.25 1 0.4 <![CDATA[Na2]]> 72.85 0.5 8.5 5.5 1 10 0.25 1 0.4 <![CDATA[Na3]]> 74.85 0.5 8.5 5.5 1 8 0.25 1 0.4

[0092] The softening point temperature and ultraviolet transmittance of the finished glass products obtained with each sample number in Table 7 were analyzed. The results are shown in Table 8.

[0093] Table 8

[0094] Sample No. Melting temperature / ℃ Softening point temperature / ℃ PCT48 (121°C, 100% humidity) transmittance attenuation <![CDATA[Na0]]> 1150 750 99.56% <![CDATA[Na1]]> 1200 820 99.75% <![CDATA[Na2]]> 1250 850 99.77% <![CDATA[Na3]]> 1300 900 99.85%

[0095] According to Table 8, as the mass ratio of Na2O / SiO2 decreases, the corrosion resistance and softening point temperature of the finished glass products are improved.

[0096] Among them, the transmittance data of different wavelengths of glass products with sample numbers Na0 and Na3 are shown in Table 9.

[0097] Table 9

[0098]

[0099]

[0100]

[0101]

[0102] It can be seen from Table 9 that the light transmittance of the photovoltaic glass after the optimization of the formula according to the embodiment of the present invention is significantly improved, wherein the comprehensive transmittance of ultraviolet light can reach 80%.

[0103] Photovoltaic modules were made using the finished glass product with sample number Na3. After aging with PID288 and DH1000, the results showed that the alkali precipitation of the glass was significantly improved, indicating that the chemical stability of the finished glass was better. The photovoltaic modules were impacted with liquid carbon dioxide at -40℃ to -55℃ at an internal temperature of 110℃, and the results showed that no cracks occurred, indicating that the Na3 glass product had excellent heat shock resistance.

[0104] In summary, in this embodiment, the components constituting the photovoltaic glass include SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, and also include ZnO and / or Li2O. By adding ZnO and / or Li2O to the glass components, wherein Li2O can replace Na2O or K2O, not only the thermal expansion coefficient of the glass is reduced, the heat resistance and strength of the glass are enhanced, but also the ultraviolet transmittance of the glass can be improved, while ZnO can reduce the thermal expansion coefficient of the glass, improve the chemical stability of the glass, and reduce the influence of Na ions on the water resistance of the glass, and can also improve the ultraviolet transmittance of the glass; therefore, the problem of low ultraviolet transmittance of the existing photovoltaic glass provided by the present invention is solved.

[0105] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.

[0106] The photovoltaic glass and its preparation method and photovoltaic module provided by the present invention are introduced in detail above. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for general technicians in this field, according to the idea of ​​the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A photovoltaic glass, characterized in that: The components constituting the photovoltaic glass include SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, and also include ZnO and / or Li2O.

2. The photovoltaic glass according to claim 1, characterized in that: In the photovoltaic glass, the mass percentage of ZnO is 0-5%.

3. The photovoltaic glass according to claim 1, characterized in that: In the photovoltaic glass, the mass percentage of ZnO is 0.5-1.5%.

4. The photovoltaic glass according to claim 1, characterized in that: In the photovoltaic glass, the mass percentage of Li2O is 0-2%.

5. The photovoltaic glass according to any one of claims 1 to 4, characterized in that: In the photovoltaic glass, the mass percentages of SiO2, Al2O3, CaO, MgO, Na2O, K2O and Sb2O3 are 70-76%, 0-1%, 5-10%, 1-6%, 5-12%, 0-2% and 0-0.5% respectively.

6. The photovoltaic glass according to claim 5, characterized in that: The components constituting the photovoltaic glass include SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, ZnO and Li2O, and the mass percentages of SiO2, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, ZnO and Li2O are 74.85%, 0.5%, 8.5%, 5.5%, 8%, 1%, 0.25%, 1% and 0.4% respectively.

7. A method for preparing photovoltaic glass, characterized in that: include: After quartz glass is granulated, Al2O3, CaO, MgO, Na2O, K2O, Sb2O3, and ZnO and / or Li2O are added and melted to obtain a first slurry; Passing a reducing gas into the first slurry for a reduction reaction to obtain a second slurry, wherein the reducing gas is a mixed gas of H2 and CO; The second slurry is clarified, homogenized, formed, processed and annealed to obtain photovoltaic glass.

8. The preparation method according to claim 7, characterized in that: The volume percentage of H2 in the reducing gas is greater than or equal to 80% and less than 100%.

9. The preparation method according to claim 7, characterized in that: The reducing gas is produced and obtained by adopting photovoltaic carbon fixation technology.

10. A photovoltaic module, characterized in that: It comprises a back plate, a solar cell and the photovoltaic glass as claimed in any one of claims 1 to 6, wherein the solar cell is located between the photovoltaic glass and the back plate.